Costs and Benefits of Mergers and Acquisitions in Improving Company Efficiency and Performance - Ermawati, Yana; Labo, Irwan Adam; Pontoh, Sahrul; ⁠Rahmi, ⁠Rahmi; Tahir, Arlan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Purpose: This study aims to evaluate the costs and benefits of mergers and acquisitions (M&A) in improving company efficiency and performance. The research focuses on financial and non-financial dimensions, including operational synergies, employee engagement, and stakeholder relations, while addressing the influence of environmental, social, and governance (ESG) considerations and technological advancements. Research Design and Methodology: This research adopts a qualitative systematic literature review (SLR) approach, synthesizing findings from peer-reviewed studies published in prominent academic journals. The study evaluates existing literature on M&A performance by identifying recurring themes related to operational efficiency, financial performance, cultural integration, and ESG impacts. This method enables a comprehensive analysis of the factors that affect M&A success, particularly in emerging markets such as Indonesia. Findings and Discussion: The study reveals that effective integration strategies are crucial for achieving operational synergies, reducing costs, and enhancing productivity. While M&A transactions can lead to economies of scale and market expansion, they also present challenges such as employee turnover, cultural conflicts, and increased operational expenses. ESG policies significantly enhance long-term resilience and stakeholder trust; however, regulatory limitations and resource constraints in emerging markets hinder their effective implementation. The findings highlight the importance of adaptive management practices and cross-functional synergy teams in ensuring successful post-merger integration. Implications: The study highlights the importance of comprehensive planning, stakeholder engagement, and ESG-driven strategies in M&A processes to optimize both financial and non-financial benefits. The results provide valuable insights for managers, policymakers, and researchers in developing frameworks for sustainable M&A practices that enhance organizational resilience and competitiveness.